COMPARATIVE EFFECTIVENESS OF PERINDOPRIL AND LOSARTAN IN PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY - S. V. Nedogoda; A. A. Ledyaeva; E. V. Chumachek; V. V. Tsoma; G. G. Mazina; A. S. Salasyuk; I. N. Barykina (Российский кардиологический журнал, 2012)
Aim. To assess the antihypertensive effectiveness of perindopril А and losartan and their influence on the main cardiovascular risk factors among patients with arterial hypertension and obesity. Material and methods. This single-blind, randomised, comparative parallel study included patients either untreated with antihypertensive medications or in the end of the two-week wash-out period. All patients were randomised (random envelope method) into 2 groups: Group I (n=30) received perindopril А (Prestarium A, Servier; 10 mg/d), while Group II (n=30) was administered losartan (Cozaar, Merck Sharp & Dohme; 100 mg/d) for 24 weeks. The examination included 24-hour blood pressure monitoring (SpaceLabs 90207, USA), the measurement of pulse wave velocity (PWV), augmentation index, and central aortal pressure (Sphygmocor), and standard echocardiography (EchoCG) (ALOKA prosound L7 premier). Results. In the perindopril А group, 24-hour levels of systolic and diastolic blood pressure (SBP, DBP) decreased by 15,2% and 18,1%, respectively; in the losartan group, this reduction was 7,8% (p<0,05) and 14,9%, respectively. Perindopril А more effectively, compared to losartan, reduced left ventricular myocardial thickness and myocardial mass index – by 5,3% and 14,3%, respectively, vs. 1,2% and 5,5% (p<0,05). Perindopril А also reduced the carotid-femoral PVW (CF PWV) by 28,9% and the carotid-radial PVW (CR PWV) by 25,8%, compared to 4,1% and 15,7% (p<0,05) in the losartan group. Augmentation index and central aortal pres in the losartan group. Augmentation index and central aortal pressure decreased by 17,4% and 7,5%, respectively, in the perindopril А group. In the losartan group, the respective figures were 3,5% and 1,3% (p<0,05). An important finding for the patients with arterial hypertension and obesity was a reduction in blood leptin levels – by 29,7% vs. 6,9% in participants treated with perindopril А vs. losartan (p<0,05). Conclusion. Perindopril А is more suitable for the arterial hypertension treatment in obese patients, since it not only more effectively, compared to losartan, reduced BP, but also demonstrated more beneficial effects on the cardiovascular risk factors in this clinical group (including normalisation of lipid and carbohydrate metabolism or improvement of anthropometric parameters).